Determinants of capital structure in UK and Chinese consumer service industry - FENG, CHUN (2013)
This paper aims to investigate the determinants of capital structure in Chinese and UK consumer service industry. This research use panel data to investigate 1618 observations of the Chinese companies and 835 observations of the UK companies in consumer service industry from 2003 to 2012. This test is run on total, long-term and short-term leverage as dependent variables. Profitability, size, growth opportunity, volatility, non-debt tax shields, collateral value of assets, uniqueness is determined as independent variables.